Nanoscale magnetic sensing with an individual electronic spin in diamond - Maze, J. R.; Stanwix, P. L.; Hodges, J. S.; Hong, S.; Taylor, J. M.; Cappellaro, P.; Jiang, L.; Dutt, M. V. Gurudev; Togan, E.; Zibrov, A. S.; Yacoby, A.; Walsworth, R. L.; et al. (Nature (London), 2008)
Spintronics: diamonds make sense A type of natural impurity in diamond crystals, called a nitrogen-vacancy centre, has a unique, long-lived single electron spin state that can be controlled and detected optically. This property can be used to create 'spintronics' devices and has possible application in quantum information processing. Two groups this week describe the application of this technology to nanoscale magnetic resonance imaging. Maze et al . demonstrate magnetic sensing using coherent control of diamond spins. They show that in principle, precision measurements of nano-tesla magnetic fields are possible, corresponding roughly to the field of a single proton at a distance of 10 nm. Balasubramanian et al . demonstrate initial steps towards a sensitive, high-resolution imaging technique using diamond spins. They show that the location of single nitrogen-vacancy spins can be determined to 5-nm resolution. In an accompanying News & Views, Michael Romalis observes that a combination of these two techniques could lead to detection and imaging of individual nuclear spins, even the structure determination for a single molecule. And as both experiments were done at room temperature, biological applications of these methods can be anticipated. A naturally occurring impurity in diamond crystals, the nitrogen-vacancy centre, has been found to have a unique, long-lived single electron spin state that can be controlled and detected optically. An approach to magnetic sensing by coherent control of such diamond spins is demonstrated, and it is shown that precision measurements of nanoTesla magnetic fields are in principle possible. Detection of weak magnetic fields with nanoscale spatial resolution is an outstanding problem in the biological and physical sciences 1 , 2 , 3 , 4 , 5 . For example, at a distance of 10 nm, the spin of a single electron produces a magnetic field of about 1 μT, and the corresponding field from a single proton is a few nanoteslas. A sensor able to detect such magnetic fields with nanometre spatial resolution would enable powerful applications, ranging from the detection of magnetic resonance signals from individual electron or nuclear spins in complex biological molecules 5 , 6 to readout of classical or quantum bits of information encoded in an electron or nuclear spin memory 7 . Here we experimentally demonstrate an approach to such nanoscale magnetic sensing, using coherent manipulation of an individual electronic spin qubit associated with a nitrogen-vacancy impurity in diamond at room temperature 8 . Using an ultra-pure diamond sample, we achieve detection of 3 nT magnetic fields at kilohertz frequencies after 100 s of averaging. In addition, we demonstrate a sensitivity of 0.5 μT Hz -1/2 for a diamond nanocrystal with a diameter of 30 nm.